Pembangkitan pola menggunakan konsep grup kertas dinding - Theophilus Wellem; Ade Iriani; Yessica Nataliani (AITI, 2021)
Two-dimensional repetitive and symmetrical patterns are found in everyday life, such as in cloth motifs, decorative art, road pavement design, and floor tiles. The repetitive and symmetrical patterns are formed by geometric transformation, which comprises translation, rotation, reflection, and glide reflection. In mathematics, the study of repetitive patterns on a plane, formed by geometric transformations, belongs to the plane symmetry group. This plane symmetry group is often referred to as plane crystallographic group or wallpaper group that comprises 17 known patterns. The purpose of this research is to generate various patterns from a basic pattern by applying the concept from the wallpaper group. Furthermore, this research also identifies four cloth motifs and categorizes them to the wallpaper group. This research was conducted by: (1) determining and creating a basic pattern that will be used to form other patterns, (2) generating 17 patterns from the basic pattern based on the patterns in the wallpaper group, (3) identifying some existing motifs downloaded from the Internet and categorize them to the wallpaper group. The basic pattern used in this research is a spiral pattern. The results obtained from this research are the 17 different spiral motifs as well as the identification of four motifs obtained from the Internet to one of the 17 patterns of wallpaper group.